Global, regional, and national burden of female infertility and trends from 1990 to 2021 with projections to 2050 based on the GBD 2021 analysis - Jie Liu; Yi Qin; Hui Liu; Yonglin Liu; Yi Yang; Yumei Ning; Huijun Ye (Scientific Reports)
Abstract Female infertility represents a significant reproductive health issue that critically affects global fertility rates. In this study, we utilized the most recent data from the Global Burden of Disease (GBD) study 2021. Initially, we assessed the global burden by the number of female infertility prevalence and disability-adjusted life years (DALYs), along with the age-standardized rate (ASR) per 100,000 individuals, stratified by age, sociodemographic index (SDI), nationality, and region. Furthermore, linear regression models were employed to examine the temporal trends of disease burden from 1990 to 2021. Cluster analysis facilitated the evaluation of disease burden change patterns across different GBD regions. Lastly, the autoregressive composite moving average model was applied to forecast future disease burdens. In 2021, the global prevalence of female infertility was estimated at 110,089,459, contributing to 6,210,145 DALYs, there was an observed increase of 84.44% in prevalence and 84.43% in DALYs since 1990. The highest burden occurred among individuals aged 35–39, with the most rapid increase observed in the 30–34 age group. The burden of female infertility displayed considerable variability across GBD regions and countries, with areas of high-medium SDI facing elevated risks. Projections indicate a continuing rise in the ASR of prevalence and DALYs for female infertility over the next 2 decades. The global burden of female infertility has intensified from 1990 to 2021, with notable disparities across different SDI regions and countries. Women aged 35–39 face the highest risk, and there is a trend toward earlier onset of infertility.